THE PROBLEM OF LEARNING FOR 11th GRADE VISUAL IMPAIRMENT STUDENTS AT SLBA BARTEMEUS MANADO - Anastasia Yesika Mamuaya; Noldy Pelenkahu; Yapi Wongkar (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study was to learn and explain English language teaching and learning for students with visual impairments in SLBA BARTEMEUS MANADO. This was a case study, and the approach used in this study was a qualitative approach, which produces descriptive data in the form of words written or spoken about the individuals and behaviours that may be observed. For this study, the researcher employed two methods of data gathering. The study’s findings included English language instruction and learning for visually impaired students in the XI grade at SLBA BARTEMEUS MANADO. This viewpoint is supported by various indicators, including: 1) In teaching and learning English, a variety of approaches, methods, techniques, and learning media are used; they include cognitive and communicative approaches, grammar translation methods, audiolingual methods, discussion methods, and Q&A methods. All of these are customized to the English lesson materials. In addition to this, a method for translating words and sentences was used, along with the best possible audio—a conversation, music, and dialogue—that the pupils could hear. and supported by suitable media, including songs, reglets, styluses, braille English textbooks, and reglets. Jaws software, a tape recorder, and Perkins Braille. 2) Obstacles and strategies for teaching and learning English in SLB-A BARTEMEUS MANADO was created by both the teacher and the pupils, and the obstacles are made up of two types: both external and internal factors. Kids’ low internal motivation and lack of confidence led to internal. The external component resulted from English education rather than special educational requirements.